Supercritical fluid extraction and gas chromatographic-mass spectrometric analysis of terpenoids in fresh kaffir lime leaf oil - Orranuch Norkaew (2018)
Fresh Thai kaffir lime leaves were subjected to extraction by supercritical carbon dioxide yielding yellow clear oils which were then analyzed by gas chromatographic-mass spectrometric technique (GC-MS). The conditions of supercritical fluid extraction (SFE); pressure, temperature, extraction time, and type and percentage of modifier which gave the highest yield of the oil were 3,000 psi, 55°C, 15 min, and 10% isopropanol, respectively. Results from GC-MS analysis revealed 21 identified terpenoids which were classified in the groups of monoterpenes, oxygenated monoterpenes, sesquiterpenes and oxygenated sesquiterpenes, each having the number of 3, 5, 9, and 4, respectively. Citronellic acid (4.5%), nerolidol (2.14%), δ-cadinene (1.49%), citronellal (1.41%) and citronellol (1.39%) were found as the major constituents in this SFE extract of fresh kaffir lime leaves.